3547 Relationship between smoking and alcohol use status: variations in candidate genes associated with addiction and successful quitting smoking. (27th March 2019) - Shaheen, Magda; Brown, Amira; Pan, Deyu; Schrode, Katrina
Abstract : OBJECTIVES/SPECIFIC AIMS: Previous studies showed that 52% of smokers were unsuccessful in quitting smoking. Smoking in alcoholics is 2-3 times that of the general population with 50%-80% of alcoholics smoking regularly. Studies have linked several genetic variants to addiction. We examined the relation between successful quitting smoking, alcohol use, and genetic data for CYP2A6, CYP2B6, DRD2, DRD1 and GABRB1 alleles. METHODS/STUDY POPULATION: We analyzed data from NHANES III 1988-1994 for socioeconomic factors, physical activity, body mass index (BMI), alcohol status, successful quit smoking, and genetic data for CYP2A6, CYP2B6, DRD2, DRD1 and GABRB1 alleles. Multivariate logistic regression was used to examine the association between successful quit smoking and genotypes adjusting for other variables. Data were analyzed using SAS version 9.3 (design & weight). RESULTS/ANTICIPATED RESULTS: Of the 2, 269 smokers, 57% were current smokers, 35% were heavy drinkers, 24% were both smokers & heavy drinkers and 41% successfully quitted smoking. Successfully quit smoking was associated with CYP2A6 (rs28399433-TG) (adjusted odds ratio (AOR) = 3.6, 95% confidence interval (CI) = 1.1-11.9, p = 0.03), CYP2B6 (rs2279343-AA and AG) (AOR = 2.3, 95%CI = 1.5-3.5, p = 0.0003 for AA & AOR = 2.3, 95%CI = 1.2-4.2, p = 0.01 for AG) and DRD1 (rs4532-AA) (AOR = 2.2, 95%CI = 1.01-4.6, p = 0.04). Among heavy drinkers, those with CYP2A6 (rs28399433-TG) and CYP2B6 (rs2279343-AA and AG) were more likely to successfully quit smoking and those with CYP2A6 (rs5031017-GG) and GABRB1 (rs1442099-CC) were less likely to successfully quit smoking (p<0.05). DISCUSSION/SIGNIFICANCE OF IMPACT: We concluded that while rs28399433-TG, rs2279343-AA & AG positively impacted the success to quit smoking, rs5031017-GG & rs1442099-CC negatively impacted the success in quitting smoking both overall and specifically in heavy drinker smokers.